Interrogating the own: a practise-based, auto-ethnographic reflection on musical creation with reference to the work of Abdullah Ibrahim, Zim Ngqawana and Kyle Shepherd - Shepherd, Kyle (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMus)--Stellenbosch University, 2018